Characterization of cephalosporin and fluoroquinolone resistant Enterobacterales from Irish farm waste by whole genome sequencing - Prendergast, Deirdre M.; Slowey, Rosemarie; Burgess, Catherine M.; Murphy, Declan; Johnston, Dayle; Morris, Dearbháile; O’ Doherty, Áine; Moriarty, John; Gutierrez, Montserrat (Frontiers in Microbiology, 2023)
The Enterobacterales are a group of Gram-negative bacteria frequently exhibiting extended antimicrobial resistance (AMR) and involved in the transmission of resistance genes to other bacterial species present in the same environment. Due to their impact on human health and the paucity of new antibiotics, the World Health Organisation (WHO) categorized carbapenem resistant and ESBL-producing as critical. Enterobacterales are ubiquitous and the role of the environment in the transmission of AMR organisms or antimicrobial resistance genes (ARGs) must be examined in tackling AMR in both humans and animals under the one health approach. Animal manure is recognized as an important source of AMR bacteria entering the environment, in which resistant genes can accumulate. To gain a better understanding of the dissemination of third generation cephalosporin and fluoroquinolone resistance genes between isolates in the environment, we applied whole genome sequencing (WGS) to Enterobacterales (79 E. coli, 1 Enterobacter cloacae, 1 Klebsiella pneumoniae and 1 Citrobacter gillenii) isolated from farm effluents in Ireland before (n=72) and after (n=10) treatment by integrated constructed wetlands (ICWs). DNA was extracted using the MagNA Pure 96 system (Roche Diagnostics, Rotkreuz, Switzerland) followed by WGS on a MiSeq platform (Illumina, Eindhoven, Netherlands) using v3 chemistry as 300-cycle paired-end runs. AMR genes and point mutations were identified and compared to the phenotypic results for better understanding of the mechanisms of resistance and resistance transmission. A wide variety of cephalosporin and fluoroquinolone resistance genes (mobile genetic elements (MGEs) and chromosomal mutations) were identified among isolates that mostly explained the phenotypic AMR patterns. A total of 31 plasmid replicon types were identified among the 82 isolates, with a subset of them (n=24), identified in E. coli isolates. Five plasmid replicons were confined to the Enterobacter cloacae isolate and two were confined to the Klebsiella pneumoniae isolate. Virulence genes associated with functions including stress, survival, regulation, iron uptake secretion systems, invasion, adherence and toxin production were identified. Our study showed that antimicrobial resistant organisms (AROs) can persist even following wastewater treatment and could transmit AMR of clinical relevance to the environment and ultimately pose a risk to human or animal health.